THE IMPACT OF FINANCIAL SECTOR REFORMS ON AGRICULTURAL AND MANUFACTURING SECTORS IN NIGERIA: AN EMPIRICAL INVESTIGATION - Obafemi, Frances Ngozi; Udah, Enang Bassey (European Scientific Journal, ESJ, 2012)
The growth finance nexus has elicited considerable debate in the academia and among policy makers. This is because, among others, the current reforms in the financial sector are based on the premise that relaxing financial constraints and deepening the financial sector is essential to promote economic growth and development. To contribute to this debate, this paper uses the variance decomposition and impulse response paradigms to test whether or not financial sector variables stimulate the growth of output in agricultural and manufacturing sectors of the Nigeria economy. The results suggest that relaxing the financial development constraints and deepening the financial sector is crucial to boost economic growth in the identified two sectors.